28 STEMMING THE DECLINE OF NON-ENGLISH LANGUAGE JOURNALS: THE FUTON EFFECT. (1st March 2005) - Murali, N. S.; Mueller, P. S.; Murali, H. R.; Erwin, P. J.; Cha, S.; Ghosh, A. K.
Abstract : Historically medical science journals in the 19th century were primarily published in German or English. With the Internet era, it appears that English has become the language of science. There is a growing concern that non-English journals are on the decline with a clear and present danger of loss in diversity as well as originality of research. The first 40 general and internal medicine journals listed under the ISI are published in English. Purpose: Full Text on the Net bias (FUTON Bias) is the "tendency to peruse what is more readily available on the net." We sought to determine if Full Text on the Net bias (FUTON Bias) might explain the decline of non-English journals and elucidate ways in which non-English journals might enhance visibility of research and scholarship. Methods: We identified all non-English journals (Spanish, Dutch, Italian, French and German) listed in ISI under Medicine, General and Internal (n = 21). We excluded Schweizerische Medizinische Wochenschrift as it has been published in English since 2001 as Swiss Medical Weekly. The on-line status of the remaining journals was ascertained in MEDLINE as FUTON, abstracts or references only. All Impact Factors from 1988 to 2003 were abstracted. Summary of Results: We observed that traditionally non-English journals that also published in English (multi-lingual) had an increase in their impact factors while those that chose not to do so maintained their base impact factors. This confirms the existence of a language bias: non-English journals tend to have lower impact factors, even in the Internet era. Interestingly however, the rise in impact factors of such multi-lingual journals paralleled in time and inception the rise of those providing FUTON and the availability of the Internet as a mode of scientific dissemination Also, the mean impact factor of multi-lingual FUTON journals was approximately threefold higher than multilingual journals that provided only abstracts or references. Conclusion: Our study suggests that non-English journals may better serve national and international audiences by becoming FUTON. Financial considerations may limit the ability of some of these journals in providing "free" FUTON. However, these non-English journals may be able to effectively disseminate scientific knowledge, improve the visibility of research and impact factors as well as stem their decline by at least providing articles on the net as FUTON. The innate tendency to pick the "low-hanging fruit of convenience" greatly enhances the odds that a FUTON article will be read or cited. By the same token, invisible research, defined as not readily accessible on-line, may possibly be ignored or overlooked and therefore disregarded.